IMPLEMENTING RAFT STRATEGY TO ENHANCE STUDENTSâ€™ SKILL IN WRITING FORMAL LETTER - Lindawaty, Januarnita; ,, Sudarsono; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: This research aims to find out how the implementation of RAFT (Role, Audience, Format and Topic) strategy enhanced the studentsâ€™ skill in writing a formal letter and to investigate how RAFT strategy improved the studentsâ€™ writings in Grade 10 â€œSMA Tunas Bangsa Kubu Rayaâ€. This research is a classroom action research. The subject of this research numbered 15 students. Having conducted three cycles of action research, the researcher found out that the teaching practice improved and the result of studentsâ€™ writing scores also improved from cycle to cycle in terms of content and language. The students were able to write more effectively as they were aware who they were writing as, to whom they were writing, what format their writing was and the topic of their writing. The students wrote more purposively and focused after being introduced to RAFT writing strategy. Keywords: RAFT, writing skill, formal letter Â  Abstrak:Penelitian ini bertujuan untuk mengetahui implementasi strategi RAFT (Role, Audience, Format and Topic) dalam meningkatkan keterampilan menulis surat resmi dan untuk menelusuri bagaimana strategi tersebut berdampak pada tulisan siswa di kelas 10 SMA Tunas Bangsa Kubu Raya. Penelitian ini dilaksanakan dalam bentuk penelitian tindakan kelas dengan 15 siswa sebagai subjek penelitian. Dalam 3 siklus yang telah dilaksanakan, ditemukan bahwa kegiatan mengajar meningkat dan nilai tulisan siswa meningkat dari satu siklus ke siklus lainnya, khususnya dalam aspek isi dan bahasa. Siswa menulis dengan lebih efektif karena mereka lebih memperhatikan peran mereka sebagai penulis, kepada siapa mereka menulis, format serta topik tulisan mereka. Siswa juga lebih memperhatikan tujuan tulisan mereka setelah strategi menulis RAFT dikenalkan pada mereka. Kata kunci: RAFT, kemampuan menulis, surat resmi